PEMBERDAYAAN KELUARGA ANAK BERKEBUTUHAN KHUSUS UNTUK MENINGKATKAN PERKEMBANGAN SENSORIK, MOTORIK, PERSEPSI VISUAL, DAN KEMANDIRIAN - Linda Harumi; Prasaja; Erayanti Saloko (LPPM AN Nuur, 2025)
Background: Children with special needs frequently encounter delays in sensory processing, motor coordination, and visual-perceptual skills, which substantially limit their ability to perform Activities of Daily Living (ADLs) independently. In this context, families—acting as primary caregivers—hold a pivotal role in fostering these developmental domains through consistent home-based stimulation. Purpose : This community engagement program aimed to strengthen family capacity by providing structured training designed to enhance their knowledge, confidence, and hands-on abilities in delivering sensory, motor, and visualperceptual stimulation, as well as supporting children’s ADL performance. Method: The intervention was conducted at Wedoro Inclusive Elementary School in East Java over a period of four weeks. Results: The program led to notable improvements in parental knowledge and motivation. Participants expressed increased confidence in applying stimulation techniques at home. While no quantitative developmental outcomes in children were measured, qualitative feedback indicated improved engagement and participation of children in daily home activities. Conclusion: Family-centered training within a community-based setting effectively builds parental competence in supporting children with special needs. This model provides a practical link between clinical recommendations and everyday home routines, promoting sustainable developmental support at the family level.